HUBUNGAN STRATEGI MEKANISME KOPING DENGAN TINGKAT KECEMASAN MENGHADAPI PEMBELAJARAN KLINIK PADA MAHASISWA SEMESTER IV PROGRAM STUDI ILMU KEPERAWATAN STIKES DIAN HUSADA MOJOKERTO - Yufi Aris Lestari; Hartin Suidah; Nur Chasanah; Elvatir Nusri Nur (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background: Coping is the process of facing the difficulties of life in an attempt to overcome or live. Coping mechanism is a mechanism that consciously or not, to use a person in coping with stress or anxiety (Weller, 2005). In fact, there are some students who cannot cope with his anxiety so well that using negative coping mechanisms strategy.Purpose: This study aimed to determine the correlation of strategy coping mechanisms dealing with anxiety level students learning in clinical studies IV semester of nursing STIKES Dian Husada Mojokerto.Method: In this study, the research design used is analytic correlation with cross-sectional approach. This study is the student population by 67 students. Sampling technique using cluster random sampling with a sample of 58 respondents. The research data was taken with HRSA questionnaire sheet and questionnaire. Analysis of data using statistical test Spearman Rho.Results: The results showed the majority of respondents (63.8%) had a maladaptive coping mechanism-strategies as many as 37 respondents and the majority of respondents (60.3%) had mild anxiety level as many as 35 respondents. Results of this study no relationship strategy coping mechanisms to face the anxiety level of clinical learning in students of fourth semester School of Nursing STIKES Dian Husada Mojokerto. This study used Spearman Rho test p value obtained was 0.013 <α = 0.05.Conclusion: From the results, there is a relationship strategy coping mechanisms to face the anxiety level of learning clinic in the fourth semester student of School of Nursing STIKES Dian Husada Mojokerto. This study provides implications for the educators that research results be used as a reference in the plan to reduce student anxiety in the face of clinical learning. Key words: Strategy coping mechanisms, level anxiety, facing student learning clinic.